2022
DOI: 10.56875/2589-0646.1024
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor T-cell Therapies in Lymphoma Patients with Central Nervous System Involvement

Abstract: Background and objective: CAR T-cell therapy has significantly improved the outcomes of patients with relapsed or refractory (R/R) B-cell non-Hodgkin lymphoma (B-NHL). However, most clinical trials excluded patients with central nervous system (CNS) involvement due to uncertain efficacy and safety. Material and methods: On January 1, 2022, we searched PubMed to identify all published literature associated with current commercial CAR T-cell therapies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The comparison between Tisa-cel versus Axi-cel in terms of toxicity or efficacy showed no differences in terms of severe CRS incidence but an increased incidence of ICANs in patients receiving Axi-cel products. This agrees with previous studies that have reported increased toxicity in patients infused with Axi-cel (37,46,47). However, no significant differences were observed in eventfree survival of patients infused with Tisa-cel or Axi-cel products.…”
Section: Discussionsupporting
confidence: 92%
“…The comparison between Tisa-cel versus Axi-cel in terms of toxicity or efficacy showed no differences in terms of severe CRS incidence but an increased incidence of ICANs in patients receiving Axi-cel products. This agrees with previous studies that have reported increased toxicity in patients infused with Axi-cel (37,46,47). However, no significant differences were observed in eventfree survival of patients infused with Tisa-cel or Axi-cel products.…”
Section: Discussionsupporting
confidence: 92%
“…Among these, 25 were assessable for ICANS. They identified that 44% (11/25) developed ICANS, and 35% presented a severe form of the syndrome ( 88 ). Furthermore, Asghar et al reported collective data from 14 studies that comprised eight retrospective studies and six single-arm prospective studies/clinical trials, with a total of 137 patients.…”
Section: Icans In Patients With Hematologic Malignancies and Cns Invo...mentioning
confidence: 99%